The potential role of platelet microparticles in atherosclerosis - Tan, Kiat T.; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2005)
The release of microvesicles (‘platelet microparticles’, PMPs) by activated platelets has been shown to be an integral part of the thrombotic process. PMPs are believed to mediate many biological processes as they possess various platelet membrane proteins and bioactive lipids. Of note, there is a growing body of evidence that PMPs are involved in all stages in the pathobiology of atherosclerosis. In addition to their role in thrombosis, PMPs may also have a pro-inflammatory effect, which promotes the development of atherosclerosis. Also, bioactive lipids in PMPs have been shown to have important effects on angiogenesis. This review summarises the various studies on the possible role of PMPs in the progression of atherosclerosis.
Keywords: Platelets; platelet microparticles; thrombosis; atherosclerosis